Efficient deep blue (CIE ∼0.08) fluorophore-based benzimidazole with hybridized local and charge transfer (HLCT) excited state for OLEDs. Issue 2 (3rd April 2022) - Devesing Girase, Jaipal; Tagare, Jairam; Mukherjee, Susmita; Chakrabrati, Tanwistha; Perumal, Ajay; Vaidyanathan, Sivakumar
Abstract : Development of efficient deep blue fluorophore with Commission Internationale de l'Eclairage (CIE)y value <0.1 is of great importance for display technology. Herein, we designed and synthesized a thermally stable deep blue emissive material 3-(2-(4′′-(1-phenyl-1 H -benzo[ d ]imidazol-2-yl)-[1, 1′:4′, 1″-terphenyl]-4-yl)-1 H -phenanthro[9, 10- d ]imidazol-1-yl)benzonitrile (MCNPIBI) by integrating moderate donor and acceptor, namely, phenanthroimidazole (PI) and benzimidazole with cyanophenyl (-CN) group at N1 position of the PI to tune the CT component in the excited states. The systematic theoretical and photophysical study reveals the MCNPIBI with hybridized local and charge transfer (HLCT) excited states. Time-dependent density functional theory (TD-DFT) calculation suggests that the reverse intersystem crossing (RISC) process in MCNPIBI occurs from high-lying triplet states to a singlet state. Furthermore, the synthesized deep blue emissive materials were employed as dopants in multilayer organic light emitting diode (OLED) devices, thus resulting in deep-blue electroluminescence (EL) with an emission wavelength of 447 nm and CIE coordinates of (0.15, 0.08), which are close to the standard values for blue emitters, as suggested by NTSC (0.14, 0.08). The OLED device displays a maximum current efficiency of 2.78 cd A −1, a maximum power efficiency of 1.94 lm W −1, and a maximum external quantum efficiency of 3.69%, respectively. In addition, the OLED device has a low turn in voltage of 3.8 V.